Vegetative spreading of sour lime tahiti citrus aurantifolia (christm) swingle per rooting sticks (1992)
At Instituto Colombiano Agropecuario - Palmira was made the present study. In the final essay was evaluated concentrations of 150 and 250 ppm of indolbutiric acid, inmersion times of 30 and 45 min., sticks with and without decreasing of leaf area, two substratum (rice's hust and a mix of soil plus sand), so also non- put covers of tinen cloth over propagation chambers of substratum soil plus sand. The percentage of caIlous formation by the kind of stimulus used, it was similar in both substratums. The best results were found in kind of stick with leaf. The answer of concentrations were similar. Time of inmersion affected in significant way the number of roots, getting six roots in average, when it's used 45 min. of inmersion.